Can a stock exchange improve corporate behavior? Evidence from firms' migration to premium listings in Brazil - de Carvalho, Antonio Gledson; Pennacchi, George G. (Journal of Corporate Finance, 2012)
Because Brazil's legal system lacked protection for minority shareholders and trading of Brazilian shares flowed to U.S. exchanges, in 2001 the São Paulo Stock Exchange, Bovespa, created three premium exchange listings that require more stringent shareholder protections. This paper examines the effects of a commitment to improved corporate disclosure and governance by firms' voluntary migration to these premium listings. Our analysis finds that a firm's migration brings positive abnormal returns to its shareholders, particularly when its shares did not have a prior cross-listing on a U.S. exchange and also when the firm chooses a premium listing with the highest standards. Migration to a premium listing also leads to a significant increase in the trading volume of non-voting shares. Firms that choose a premium listing tend to have growth opportunities that they finance with subsequent seasoned equity offerings. These results suggest that a premium listing is a mechanism for bonding to improved corporate behavior that can be less costly than cross-listing on a U.S. exchange.